Determinan Kemiskinan di Negara-Negara ASEAN: Analisis Data Panel Periode 2000–2024 - Agil Mahardika Putra (JURNAL ILMIAH EDUNOMIKA, 2026)
Despite continued economic growth in ASEAN, poverty remains a problem in several member countries. This study uses panel data from ASEAN countries for the period 2000–2024 to analyze the effects of FDI, private sector domestic credit, education, urbanization, and GDP per capita on poverty. Based on the model selection, the Fixed Effect Model is the most appropriate approach. The results show that private sector domestic credit, education, urbanization, and GDP per capita are associated with poverty reduction, while FDI has no significant effect. These findings emphasize the importance of improving financial access, education, productive urbanization, and community income in supporting poverty alleviation in the ASEAN region.